2015
DOI: 10.1590/0104-1169.0144.2520
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of non-adherence to medication treatment for systemic arterial hypertension in urban and rural populations

Abstract: OBJECTIVE: to evaluate the indexes and the main factors associated with non-adherence to medication treatment for systemic arterial hypertension between urban and rural areas. METHOD: analytical study based on an epidemiological survey with a sample of 247 hypertensive residents of rural and urban areas, with application of a socio-demographic and economic questionnaire, and treatment adherence assessment. The Pearson's Chi-square test was used and the odds ratio (OD) was calculated to analyze the factors rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
2
16
0
10
Order By: Relevance
“…It is considered that the lack of hypertension control association with the vast majority of questions in Table 2 should not be considered in the evaluation of hypertensive patients. There was significant degree of agreement as a complicating factor for treatment with important issues in drug area, such as forgetting to take medication and complex schedules, results found in other studies (12)(13) . Accordingly, the fixed drug combination is a strategy that increases the adherence (14) .…”
Section: Discussionsupporting
confidence: 63%
“…It is considered that the lack of hypertension control association with the vast majority of questions in Table 2 should not be considered in the evaluation of hypertensive patients. There was significant degree of agreement as a complicating factor for treatment with important issues in drug area, such as forgetting to take medication and complex schedules, results found in other studies (12)(13) . Accordingly, the fixed drug combination is a strategy that increases the adherence (14) .…”
Section: Discussionsupporting
confidence: 63%
“…Older patients were found to be more adherent to RA treatment . However, other studies on RA patients showed that younger patients were more likely to be adherent . De Vera et al .…”
Section: Discussionmentioning
confidence: 95%
“…En relación con la edad y el sexo, en este estudio no se encontraron diferencias en el nivel de adherencia al estratificar por estas condiciones, a diferencia de lo reportado en la literatura en donde se refiere que los hombres con menor edad y menor tiempo con la enfermedad tienden a tener una menor adherencia; algunos destacan que por cada 10 años con el proceso de enfermedad la adherencia aumenta, siendo los 60 años o más donde hay mejor cumplimiento[29][30][31][32][33] . A pesar de los resultados de nuestro estudio, consideramos que estas variables deben ser tenidas en cuenta al momento de brindar educación y de implementar estrategias para aumentar la adherencia en este tipo de población.Dentro de las fortalezas de este estudio resaltamos la medición de aspectos más allá del abordaje farmacológico del régimen terapéutico en personas con HTA y DM tipo 2, incluyendo indicadores relacionados con la dieta, ejercicio, control de conductas que potencian la patología, supervisión del estado de enfermedad, efectos terapéuticos entre otros.…”
unclassified